2018
DOI: 10.1016/j.jtemb.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the zinc binding tubulin polymerization promoting protein in the mice and human eye

Abstract: Tubulin Polymerization Promoting Protein (TPPP/p25) modulates the dynamics and stability of the microtubule network by its bundling and acetylation enhancing activities that can be modulated by the binding of zinc to TPPP/p25. Its expression is essential for the differentiation of oligodendrocytes, the major constituents of the myelin sheath, and has been associated with neuronal inclusions. In this paper, evidence is provided for the expression and localization of TPPP/p25 in the zinc-rich retina and in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…TPPP/p25 localization in nerve terminals of mice and human retina has been identified; OLGs in the myelin ensheathment of optic nerve, postsynaptic nerve terminals in striations of the inner plexiform layer and a subset of amacrine cells showed immunopositivity for TPPP/p25 both in mice and human eyes [36]. The co-localization of TPPP/p25 with acetylated tubulin was detected in amacrine cells, OLG cell bodies and in synapses in the inner plexiform layer that is rich in neuropil, in which the occurrence of TPPP/p25 has been detected.…”
Section: Tppp Homologs Are Extensively Wide-spreadmentioning
confidence: 97%
“…TPPP/p25 localization in nerve terminals of mice and human retina has been identified; OLGs in the myelin ensheathment of optic nerve, postsynaptic nerve terminals in striations of the inner plexiform layer and a subset of amacrine cells showed immunopositivity for TPPP/p25 both in mice and human eyes [36]. The co-localization of TPPP/p25 with acetylated tubulin was detected in amacrine cells, OLG cell bodies and in synapses in the inner plexiform layer that is rich in neuropil, in which the occurrence of TPPP/p25 has been detected.…”
Section: Tppp Homologs Are Extensively Wide-spreadmentioning
confidence: 97%
“…Similar to Ringer, TPPP in zebrafish has been implicated in axon outgrowth (Aoki et al, 2014; Orosz, 2015). While a recent report described TPPP localization in nerve terminals of mice and human retina (Tripon et al, 2018), the role of Ringer or any TPPP family of proteins in other species in regulating MT organization during synaptic development and function remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated IOP seems to decrease the MAP1A amount and, thereby, the number of axonal cross-bridges, leading to microtubule instability and abnormal organelle transportation in axon plasma [ 72 ]. TPPPs show extensive MT bundling and polymerization abilities critical for axon formation, extension, and guidance at nerve terminals, as demonstrated in retinae of the model organisms drosophila, zebrafish, mouse, and human [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. A study investigating AD showed TPPP down-regulation [ 80 ].…”
Section: Discussionmentioning
confidence: 99%